2022
DOI: 10.3390/galaxies10010010
|View full text |Cite
|
Sign up to set email alerts
|

On the Polarisation of Radio Relics

Abstract: Radio relics are extended radio emission features which trace shock waves in the periphery of galaxy clusters originating from cluster mergers. Some radio relics show a highly polarised emission, which make relics an excellent probe for the magnetisation of the intra-cluster medium. The origin of the relic polarisation is still debated. It could be a result of tangentially stretching the magnetic field at the shock surface. This scenario would naturally explain the alignment of the polarisation (E-vectors) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…These findings have been used by Hoeft et al [223] to derive an analytical model for the polarised emission of radio relics. This model yields the result that the shock compression scenario indeed provides a plausible explanation for the radio relic polarisation.…”
Section: Polarisationmentioning
confidence: 98%
“…These findings have been used by Hoeft et al [223] to derive an analytical model for the polarised emission of radio relics. This model yields the result that the shock compression scenario indeed provides a plausible explanation for the radio relic polarisation.…”
Section: Polarisationmentioning
confidence: 98%
“…They found that the fractional polarization is crucially affected by the magnetic field strength, which influences the decrease downstream, while the shock strength has little effect on the fractional polarization. Shock compression is a plausible scenario that can explain the radio relic polarization [10].…”
Section: Galaxy Clusters Groups and Diffuse Emissionmentioning
confidence: 99%